Load characteristics of sprint interval training according to 400m running performance: Competitive level comparison - Okudaira, M.; Kuki, S.; Takuya, Y.; Fukuda, D. H.; Tanigawa, S. (International Journal of Sport & Health Science, 2019)
This study aimed to compare the load characteristics of sprint interval training (SIT) according to 400-m sprint performance. Eight elite sprinters and ten sub-elite sprinters were separated according to 400-m sprint performance and participated in this study (age: 21.0 ± 2.5 years, height: 176.0 ± 4.0 cm, and body mass: 67.0 ± 5.3 kg). All subjects performed two different SIT protocols on a cycle ergometer. The SIT protocols consisted of two bouts of 20-s maximal sprints interspersed with either 30-s rest (R-30s) or 60-s rest (R-60s). Mean power output over both sprints in R-60s was significantly greater than in R-30s in both groups (p < 0.001). In the elite group, blood lactate did not significantly differ between R-30s and R-60s even though different mean power output was recorded. However, in the sub-elite group, blood lactate from the R-60s condition was significantly greater than from the R-30s condition (p < 0.05). These results indicate different physiological responses to SIT depending on 400-m sprint capabilities. To enhance anaerobic adaptations, it is suggested that elite 400-m sprinters should utilize SIT with very short recovery periods, while sub-elite 400-m sprinters should utilize relatively longer recovery periods